Exploring how IBCLCs manage ethical dilemmas: a qualitative study - Noel-Weiss, Joy; Cragg, Betty; Woodend, A Kirsten (Université d'Ottawa | University of Ottawa, 2012)
Background: Professional health care practice should be based on ethical decisions and actions. When there are competing ethical standards or principles, one must choose between two or more competing options. This study explores ethical dilemmas experienced by International Board Certified Lactation Consultants. Methods: The investigator interviewed seven International Board Certified Lactation Consultants and analyzed the interviews using qualitative research methods. Results: "Staying Mother-Centred" emerged as the overall theme. It encompassed six categories that emerged as steps in managing ethical dilemmas: 1) recognizing the dilemma; 2) identifying context; 3) determining choices; 4) strategies used; 5) results and choices the mother made; and 6) follow-up. The category, "Strategies used", was further analyzed and six sub-themes emerged: building trust; diffusing situations; empowering mothers; finding balance; providing information; and setting priorities. Conclusions: This study provides a framework for understanding how International Board Certified Lactation Consultants manage ethical dilemmas. Although the details of their stories changed, the essence of the experience remained quite constant with the participants making choices and acting to support the mothers. The framework could be the used for further research or to develop tools to support IBCLCs as they manage ethical dilemmas and to strengthen the profession with a firm ethics foundation.
Keywords: Breastfeeding; Ethical dilemmas; Ethics; Lactation consultant; Morality; Qualitative research